J. Donald Gillaspey letter to Thomas H. Kent, May 30, 1985, regarding bird sightings - Gillaspey, J. Donaldet al (1985)
Letter discusses sightings of Pileated Woodpecker recorded in the accompanying field notes. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1985. Epson - sheet feed/flatbed